Dietary Patterns Differentially Affect Microbiome Composition and Function in a Porcine Model of Obesity-related Metabolic Disorder (OR23-04-19). (13th June 2019) - Solano-Aguilar, Gloria; Shao, Jonathan; Urban, Joseph; Lakshman, Sukla; Jang, Saebyeol; Lozano, Victoria; Sikaroodi, Masoumeh; Gupta, Richi; Gillevet, Patrick; Molokin, Aleksey; Vinyard, Bryan; Humphrys, Michael; et al.
Abstract: Objectives: To determine the impact of two isocaloric diets containing (38%, 15% and 47% energy from fat, protein and carbohydrate, respectively): Western diet (WD) rich in saturated fat, refined carbohydrate, low in fiber and high in cholesterol, and a heart healthy diet (HHD) rich in unsaturated fat, unrefined carbohydrate, fruits/vegetables, high in fiber and low in cholesterol, on the composition and function of the gut microbiome Methods: Thirty-Ossabaw pigs were fed WD or HHD diets with half within each group therapeutically treated with statin (atorvastatin [Lipitor]). The fecal microbiome was analyzed one and six months after dietary intervention by 16S rRNA sequencing and metagenomic function was empirically inferred Results: Genus diversity was transiently affected with a reduced Shannon Diversity index one month after feeding the WD or HHD (FDR P < 0.05) with no change between groups at 6 months. Bacterial communities were clustered and separated by diet independent of gender and separated by treatment with statin in the HHD only. Verrucomicrobiaceae (Akkermansia) and Methanobacteriales (Methanobrevibacter) were increased in pigs as early as one month after feeding the HHD, as was Clostridiales and Bifidobacterium (associated with optimal intestinal health). There was an enrichment of Proteobacteria (Succinivibrionaceae, Desulfovibrionaceae) in pigs fed the WD. Additional members of the Firmicutes phylum were detected. Diet-dependent associations (all P < 0.05) were identified between Lachnospiraceae members and early host dyslipidemia, inflammation, and atheromatous lesions in the left anterior descending proximal (LAD) and LAD/Left circumflex (LCX) bifurcation six months post-intervention. Conclusions: These data document for the first time a distinctive bacterial profile in Ossabaw pigs with a diet-induced dyslipidemia and early stage atherosclerosis. Taken together these results represent a new model to examine mechanistic pathways of dietary patterns and/or drug interactions and its effect on modulating microbiome in developing atherosclerosis. Funding Sources: USDA project 8040-51530-056-00 and Inter Agency USDA Agreement 588-1950-9-001 between BHNRC and Jean Mayer USDA-HNRCA